Respiratory symptoms, sensitisation and occupational exposure in the shrimp processing industry - Fikirte Debebe Zegeye; Fikirte Debebe Zegeye; Pål Graff; Miriam Grgic; Steen Mollerup; Anani Komlavi Afanou; Berit Elisabeth Bang; Berit Elisabeth Bang; Karl-Christian Nordby; Anne Straumfors; Johanna Samulin Erdem (Frontiers in Allergy)
IntroductionShellfish processing workers are highly susceptible to respiratory illnesses such as allergies and asthma. This study examined respiratory symptoms and biomarkers of allergy and asthma in Norwegian shrimp processing plant workers and evaluated allergenic and irritant protein exposures in the workplace.Material and methodsThe study included 35 shrimp processing workers and 21 controls. Respiratory symptoms were assessed via questionnaire; blood samples were analysed for allergy and asthma biomarkers and specific IgE levels. Air samples were analysed for protein levels and composition.ResultsShrimp processing workers had four to five times higher odds of reporting acute upper and chronic lower respiratory symptoms than the controls. They also had significantly higher plasma levels of IL4, CCL20, CSF2 and MMP12, with 11% of the exposed workers showing elevated levels of shrimp and crab specific IgE. Furthermore, exposed workers showed increased plasma levels of SFTPD and CHI3L1 post-shift. The median total protein exposure was 6 µg/m3, with peaks up to 66 µg/m3 in the cooking and peeling department. Total protein levels were correlated with CCL20, IL13, and basophil counts. Ninety-five shrimp proteins were identified, including seven known and eight potential allergens. Tropomyosin levels were generally high, particularly in the cooking and peeling department.ConclusionShrimp workers had a higher prevalence of respiratory symptoms and biomarkers of allergy and asthma. The work environment contained tropomyosin and other allergenic proteins as well as irritants, highlighting the need for protective measures, especially in the cooking and peeling departments.